ALOE VERA ATTENUATES GENTAMICIN-INDUCED NEPHROTOXICITY IN WISTAR ALBINO RATS: HISTOPATHOLOGICAL AND BIOCHEMICAL CHANGES - Virani, Shalini; Bhatt, Shaily; Saini, Manish; Saxena, Kk (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: To evaluate the nephroprotective properties of ethanol extract of leaves of Aloe vera against gentamicin-induced nephrotoxicity in rats. Methods: Nephrotoxicity was induced in Wistar rats by intraperitoneal administration of gentamicin 40 mg/kg/days for 5 days. Effect of concurrent administration of ethanol extract of leaves of A. vera at a dose of 20 ml/kg/day given by oral route was determined using serum creatinine and blood urea nitrogen as biochemical indicators of renal damage; after 10, 20, and 30 days. The study included a control group which received oral saline only, gentamicin treated group, received gentamicin and oral saline and A. vera group, received oral A. vera prior to gentamicin administration. Each group had six rats. Results: It was observed that in A. vera treated rats, prevented elevation of the biochemical indicators of nephrotoxicity and significantly reduced histopathological scores. Conclusion: Ethanol extract of A. vera contains constituents with nephroprotective activities. Keywords: Gentamicin-induced nephrotoxicity, Aloe vera, Wister rats, Histopathological change.